ACCULTURATION OF HADRAH WITH TRADITIONAL MALAY PERCUSSION IN ARBAIN'S MAULID ACTIVITIES IN MEDAN - Muhammad Habibur Ridho; Vanesia Amelia Sebayang; Pulumun P Ginting (Universitas Negeri Medan, 2025)
This research is entitled